Severe plastic deformation driven nanostructure and phase evolution in a Al0.5CoCrFeMnNi dual phase high entropy alloy. (December 2017) - Reddy, T.S.; Wani, I.S.; Bhattacharjee, T.; Reddy, S.R.; Saha, R.; Bhattacharjee, P.P.
Abstract: The effect of severe plastic deformation on microstructure and phase evolution was investigated in a dual phase Al0.5 CoCrFeMnNi high entropy alloy (HEA). For this purpose, the as-cast HEA was subjected to initial thermo-mechanical processing by warm-rolling and annealing. The annealed dual phase alloy showed FCC and B2 phases. The B2 phase was enriched with Ni and Al, while the converse held good for the FCC phase. These annealed HEA specimens were severely deformed by high pressure torsion (HPT) up to five complete rotations (R). The severely deformed HEA revealed nanostructured FCC grains containing nano-twinned regions and coarser B2 phase. The nanostructure formation in the softer FCC phase was attributed to greater strain partitioning and propensity for the formation of nano-twins. Although with increasing rotations, the hardness difference between the edge and centre region was reduced, the 5R HPT processed specimens showed inhomogeneity featured by intermittent hardness spikes. Upon annealing, recrystallized dual phase microstructure was confirmed in the 5R HPT processed specimen. Microstructural differences between centre and edge regions were revealed by way of large B2 clusters (5 μm-10 μm) at the centre region. Remarkably, annealing resulted in the formation of a (Fe, Cr) rich σ-phase. The formation of σ-phase resulted in much greater hardness inhomogeneity in the annealed material as compared to the 5R HPT processed material. Highlights: Effect of HPT in (FCC + B2) Al0.5 CoCrFeMnNi dual phase HEA investigated. Nanocrystalline FCC and coarser B2 phase after 5 HPT rotations. Annealing leads to precipitation of (Fe, Cr) rich σ phase. σ Phase precipitation leads to pronounced hardness inhomogeneity.